SUCCESSFUL RESOLUTION OF THYROID STORM FROM TSHoma WITH SOMATOSTATIN RECEPTOR LIGAND - Chiew, Ken Seng; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Paramasivam, Sharmila; Lim, Lee Ling; Vethakkan, Shireene; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Thyroid-stimulating hormone (TSH)-secreting pituitary adenomas (TSHomas) account for 2% of all pituitary adenomas. Symptoms of hyperthyroidism are common but thyroid storm is extremely rare. We report a case of TSHoma complicated by thyroid storm that was managed with somatostatin-receptor-ligand (SRL). CASE A 76-year-old male with TSHoma measuring 15 mm x 15 mm x 14 mm was conservatively managed for 5 years with cabergoline as he refused surgery. He presented early this year with fever, atrial fibrillation with rapid ventricular response and pneumonia requiring noninvasive ventilation. Burch-Wartofsky score was 60, consistent with thyroid storm. His fT4 and fT3 were 69.8 pmol/L (11.5-22.7 pmol/L) and 21.7 pmol/L (3.5-6.5 pmol/L) respectively. TSH was inappropriately normal at 3.74 mIU/L (0.55-4.78mIU/L). In intensive care, intravenous octreotide infusion at 50 mcg/hour was commenced. After 48 hours, ft4, ft3 and TSH reduced to 46pmol/L, 6.8 pmol/L and 0.52 mIU/L, respectively. Intravenous octreotide was converted to subcutaneous short-acting octreotide, titrated up to 100 mcg TDS. Glucocorticoids, carbimazole and betablockers were also used. After 5 days, his fT4, fT3 and TSH markedly reduced to 18.7 pmol/L, 4.2 pmol/L and 0.32 mIU/L, respectively. He was then overlapped with subcutaneous long-acting lanreotide. Repeat imaging showed unchanged size and extent of the macroadenoma. Despite re-counselling for surgery, he opted for long-term lanreotide and remains controlled to date. Only three cases of TSHoma complicated by thyroid storm have been reported. In all cases, thyroid storm occurred after transsphenoidal surgery. Thionamides and betablockers were the mainstay of therapy. To our knowledge, our case is the first to use intravenous octreotide infusion in the acute management of thyroid storm. As TSHomas express somatostatin receptors (SSTR), especially SSTR 2 and SSTR 5, SRLs target these receptors to reduce TSH secretion. CONCLUSION Thyroid storm is an extremely rare complication of TSHoma. In this case, the use of short-acting SRL in conjunction with short-term antithyroid drugs, glucocorticoids and betablockers were efficacious in the acute management of this emergency.